The Incorporation Of Multi-Lane Free Flow System Need Analysis And Challenges - Azmi, Nur Syazana (Universiti Sains Malaysia, 2022)
The multi-lane free flow (MLFF) is a system that allow highway users pay to drive through free flow without stopping. With MLFF, the toll lanes at toll plazas can be replaced with regular segments of multilane roads. Tags with readers are used with gantries across the highway to detect vehicles and to deduct tolls from vehicles using the Electronic Toll Collection (ETC), Traffic congestion at toll plazas on expressways is a regular condition on transportation networks and happens when more people use the tolled expressway. It is characterized by slower speeds, longer trip times, and more automobiles in queues. An Expressway is supposed to be an alternative for road’s user to use to avoid jams and to have faster travel time but due to the inefficient toll’s payment system, congestion have occurred on expressways. This study attempts to understand the concept of Multi-Lane Free Flow system to reduce traffic congestion at toll plazas and on Malaysia’s expressway as well as to identify the challenges of implementing the system in Malaysia. The data from survey shows that the expressway performance in Malaysia is not satisfactory. This is due the payment system is inefficient and still causes congestion even though there are so many alternatives for payment. This project review various study based on previous research on the design and challenges in implementing MLFF in other countries, interviews’s highway concessionaire for deep knowledge of implementing MLFF, analyse the road user’s satisfaction with the performance of current toll payment system in Malaysia and their perspective on MLFF system. Based on the findings, the research study shows that MLFF system has proven to be successful in other countries, as it has helped in preventing congestion. The study also shows that the challenges of implementing the MLFF in Malaysia includes the challenges of enforcement and the challenges of having sufficient fund from the government to manage the new technologies such as RFID. Malaysia’s technology is still in relatively behind other countries. The road’s infrastructure in Malaysia need to be reformed due to poor design and the new legislation need to be made to avoid leakages from occurring.